Persuasion Knowledge: A Cognitive Resource against Anti-Smoking Persuasion - Boukamcha, Fayçal (International Journal of Economic Practices and Theories, 2014)
The purpose of the paper is to explain resistance to anti-smoking persuasion by integrating persuasion knowledge as a cognitive resource that likely affects persuasive message efficiency. A research model was designed including an anti-smoking persuasive message, persuasion knowledge, coping self-efficacy and attitude certainty as predictors of resistance to anti-smoking persuasion. A survey was conducted on a convenience sample of 617 Tunisian smokers. The sample was divided into two subgroups: the first one was exposed to a high negative anti-smoking print ad; the second was exposed a low negative anti-smoking print ad. The constructs were measured on a 5 points’ Likert scales and were one-dimensional except for the resistance to persuasion scale that contained 3 attitudinal dimensions: cognitive, affective and behavioral. To assess the research model, the Partial Least Square (PLS) method was used. According to the findings, the print ads weren’t effective in activating persuasion knowledge. Nevertheless, persuasion knowledge was high and positively correlated with the cognitive and the behavioral component of resistance to the anti-smoking persuasion when channeled through attitude certainty.